Constraining the TeV Halo Population in M31 - Andrés, A.; Albert, A.; Alfaro, R.; Alvarez, C.; Arteaga-Velázquez, J. C.; Avila Rojas, D.; Ayala Solares, H. A.; Babu, R.; Belmont-Moreno, E.; Caballero-Mora, K. S.; Capistrán, T.; Yun-Cárcamo, S.; et al. (Proceedings of Science, 2024)
TeV halos are a new class of γ-ray sources recently observed around some middle-aged pulsars. They are extended γ-ray emission regions with a size bigger than the Pulsar Wind Nebulae but smaller than a Supernova Remnant. Several studies indicate that a TeV halo may be a general signature around a middle-aged pulsar, but this is still an open question. Some recent results suggest TeV halos are significantly contributing to the TeV emission of our Galaxy, and models have been proposed to reproduce the observed population of TeV halos in the Milky Way. In this work, we analyze the emission at TeV energies of the Andromeda galaxy (M31), the closest spiral galaxy to Earth. M31 has also been observed to have a GeV excess similar to the observed in the Galactic Center of our Galaxy. The aim of this work is to model the γ-ray emission at TeV energies in M31 assuming both the Milky Way and M31 share similar properties. Using 6 years of HAWC observations, we compute the flux upper limits in the region of M31 at TeV energies.
CRIS-Team Scopus Importer:2025-02-04